Clinical pharmacist and pharmaceutical interventions in HBH unit: a French observational study. Issue 4 (4th July 2021) - Belaiche, Stéphanie; Goulois, Stéphanie; DeBerranger, Eva; Odou, Pascal; Balagny, Sara; Décaudin, Bertrand
ABSTRACT: Objectives : Home-Based Hospital (HBH) services concern patients of all ages suffering from conditions requiring technical care, close clinical monitoring, or hospital treatments that would normally be provided during hospitalisation. Drug-related problems are common in chronically-ill patients and many such events are preventable. Nevertheless, little data is available for outpatients, especially for HBH unit patients. The aim of the study was to assess the rates and types of drug-related problems prevented and resolved by the clinical pharmacist in a Home-Based Hospital unit. Methods : The drug-related problems were registered prospectively by the clinical pharmacist from May 2011 to April 2015. These pharmaceutical interventions were analysed according to the intervention tool recommended by the French Society of Clinical Pharmacy (Act IP). Results : 20, 195 medication prescriptions relating to 2, 878 patients were analysed. We registered 388 drug-related problems involving 267 patients (71.2% female; mean age 32.1 ± 29.7 years), mainly concerning untreated conditions (24.2%), drugs used without indications (14.7%), non-conformity to guidelines or contra-indication (12.6%) and drug monitoring (12.4%). Pharmaceutical interventions involved 186 drugs, mainly for hematopoiesis, infections and the digestive system (34%, 16.5%, and 14.6%, respectively). 87.6% of the pharmacist's recommendations were accepted. Conclusions : A formatted clinical pharmacist evaluation was able to detect a high level of drug-related problems, and prevent complications in patients cared for by a Home-Based Hospital unit.